The Influence Of Work Life Balance, Professional Competence, Preventive Discipline And Financial Compensation On The Employee Performance - Nabila Idvina Ayu; Mehrunnisa Nosi; Ermawati Laili; Umami Farida Riza (SHS Web of Conferences)
Teachers are human resources who are considered the key to success or efforts to achieve educational goals. Therefore, education as a whole requires reliable human resources, namely professional teachers. Education cannot make a meaningful contribution without the support of professional and qualified teachers. This study is done to identify the effect of work life balance, professional competence, preventive discipline and financial compensation on the performance of MTs NU 10 Penawaja teachers. This study’s methodology is survey-based and quantitative. Both primary and secondary data were used. The study’s sample size consists of 36 MTs NU 10 Penawaja instructors. A linkert scale was then used to rate the respondents’ responses. Multiple linear regression is the analytical technique employed in this study, with the assistance of the SPSS version 25 program. The analysis used includes validity test, classical assumptions, reliability test, hypothesis testing. The results of this study are work life balance has a positive effect on teacher performance, professional competence has a positive effect on teacher performance, preventive discipline has a positive effect on teacher performance and financial compensation has a positive effect on teacher performance.